2019
DOI: 10.3390/nu11050976
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the Mediterranean Diet is Associated with Better Sleep Quality in Italian Adults

Abstract: Background: Sleep quality has been associated with human health and diseases, including cognitive decline and dementia; however major determinants of sleep disorders are largely unknown. The aim of this study was to evaluate the association between sleep quality and adherence to the Mediterranean dietary pattern in a sample of Italian adults. Methods: A total of 1936 individuals were recruited in the urban area of Catania during 2014–2015 through random sampling. A food frequency questionnaire and validated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
93
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(105 citation statements)
references
References 82 publications
8
93
1
3
Order By: Relevance
“…We show here that greater consumption of these foods is predictive of markers of better sleep quality, including higher sleep efficiency. These findings support associations of fruit and vegetable intake with sleep quality in cross-sectional studies [17,34], and suggest a potential for increased fruit and vegetable intake to improve sleep quality, although experimental research is needed to confirm this. The high nutrient density of fruits, vegetables, and legumes may underlie their associations with sleep quality.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…We show here that greater consumption of these foods is predictive of markers of better sleep quality, including higher sleep efficiency. These findings support associations of fruit and vegetable intake with sleep quality in cross-sectional studies [17,34], and suggest a potential for increased fruit and vegetable intake to improve sleep quality, although experimental research is needed to confirm this. The high nutrient density of fruits, vegetables, and legumes may underlie their associations with sleep quality.…”
Section: Discussionsupporting
confidence: 67%
“…The current study was designed to prospectively assess whether adherence to a Mediterranean diet modified for US populations (aMed) [12] predicts habitual sleep quality in US women, who generally report more sleep-related complaints than men [22]. Additionally, given previous cross-sectional associations of foods and nutrients encouraged in an aMed diet (e.g., fruits and vegetables, unsaturated fat) with parameters of sleep quality [6,17], we aimed to assess whether aMed diet components, or their key nutrients, were associated with future sleep quality. We hypothesized that greater concordance to the aMed diet at baseline would be associated with better overall sleep quality, highlighted by shorter sleep onset latency, higher sleep efficiency, and fewer sleep disturbances, at 1-y.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies focusing on adherence to the Mediterranean diet, quality and duration of sleep, and insomnia in older adults have been carried out [ 53 , 54 , 55 , 56 ]. These authors point out improvements in sleep quality, duration, and reduced insomnia with high adherence to the Mediterranean diet.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary (poly)phenols have been related to several potential health benefits [20]: recently, they have been hypothesized to also play a role in brain health [21,22]. We previously reported that individuals more adherent to healthy dietary patterns (i.e., the Mediterranean diet) and to a diet with low inflammatory potential were more likely to have higher sleep quality [23,24]. In the present study, we aimed to test whether total, subclasses of and individual (poly)phenols may be candidate molecules associated with sleep quality in a cohort of Italian adults.…”
Section: Introductionmentioning
confidence: 99%